IDENTIFICATION OF SOME COMPOSITE MEDICINAL DRUGS CONTAINING PARACETAMOL, WITH IR-SPECTROMETRY METHOD - A. S. Saushkina; L. N. Zinchuk; M. A. Denisov; V. A. Shokurov; D. V. Goncharov (Фармация и фармакология (Пятигорск))
A serious threat to the health of the population is falsified medicines. In a number of cases, they are identified in the process of incoming quality control for compliancewith the requirements of regulatory documents for indicators “Description”, “Packaging”, “Marking”. However, in order to identify sophisticated counterfeits, only a visual assessment of the drug is not enough. Purpose screening evaluation of potentiallycounterfeited or poor-quality drugs using the IR spectrometry along the total spectrum.Materials and methods. The objects of research were available in freely availablecommercially available tablets produced by domestic and foreign manufacturers“Paracetamol Extratab”, “Solpadein fast”, “Citrapac”, “Citramon P”, “Ascofen-P”,  corresponding to the requirements of the current regulatory documents. The studies were carried out on a Fourier-Spectrophotometer infrared “FSM 1201”. Results and discussion. On the example of the tablets “Citramon P”, “Ascophen-P”, “Citrapac”, “Paracetamol Extratab”, “Solpadein Fast” the possibility of using the total IR spectra as a primary screening index of authenticity is shown. It was established that the total IR spectra of medicines of similar composition reflect the similarity of serial samples of the products ofone manufacturer and the difference in serial samples of products of different manufacturers.